2012
DOI: 10.1158/1541-7786.mcr-11-0488
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genomic Targets of Transcription Factor Aebp1 and its role in Survival of Glioma Cells

Abstract: A recent transcriptome analysis of graded patient glioma samples led to identification of AEBP1 as one of the genes upregulated in majority of the primary GBM as against secondary GBM. Aebp1 is a transcriptional repressor that is involved in adipogenesis. It binds to AE-1 element present in the proximal promoter of aP2 gene that codes for fatty acid binding protein (FABP4). A comprehensive study was undertaken to elucidate the role of AEBP1 overexpression in glioblastoma. We employed complementary gene silenci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Similarly, SULT4A1, with lower expression in children brain tumor [39], is regulated positively by NFIL3 in normal samples while negatively by NFIL3 in NG group. The negative regulation relationship between NFIL3 and NGEF in NG group, and the lower expression of NGEF was also observed, which is consistent with the previous report [40]. …”
Section: Resultssupporting
confidence: 92%
“…Similarly, SULT4A1, with lower expression in children brain tumor [39], is regulated positively by NFIL3 in normal samples while negatively by NFIL3 in NG group. The negative regulation relationship between NFIL3 and NGEF in NG group, and the lower expression of NGEF was also observed, which is consistent with the previous report [40]. …”
Section: Resultssupporting
confidence: 92%
“…For the CMT-93-specific TFs, the analysis reported the master regulators Aebp1 (ACLP), Il2rg (gamma-c) and Mapk1 (ERK2), which reach 43, 36, and 31 TFs from the set, respectively. The first proposed master regulator, Aebp1, is known to act as a transcriptional repressor in adipogenesis (Ladha et al, 2012 ). Aebp1 is upregulated in the majority of the primary glioblastoma multiforme (GBM) and loss of Aebp1 function was shown to result in apoptosis (Ladha et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the constitutive expression of AEBP1 in brain tissue, previous reports have shown that AEBP1 protein is expressed in the choroid plexus of embryos and in some glioma cell lines . However, the expression profile of the AEBP1 protein in adult brains has not yet been examined.…”
Section: Discussionmentioning
confidence: 99%